Welcome Letter - ALUAȘ, Maria (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
On behalf of the planning committee of the Annual EACME Conference, it is my pleasure to welcome you in Cluj-Napoca, the heart of Transylvania! This is the 37th Annual Conference on Medical Ethics and Bioethics, held for the first time in Romania and after 27 years in one of the East European countries. This year EACME is organized by Iuliu Hațieganu University of Medicine and Pharmacy in partnership with the Babes-Bolyai University. The theme – Smart Ethics. Trends to the Future, chossen for 2020 EACME conference – has been very attractive, especial in the actual international context. Due to the COVID-19 pandemic the 2020 annual conference was postponed, to figure out how to organize such event, but even keep participants and organizers safe from possible infections. And now, for the first time in history, we will be offering participants the flexibility to choose between attending the conference venue physically, and joining the event virtually through the online events platform. 167 abstracts have been submitted, 120 have been confirmed, 26 countries from 3 continents are represented, 4 plenary sessions and 32 scientific sessions will present a wide selection of distinguished speakers.